THE LACTIC ACID BACTERIA OF BEBONTOT SPENT CHICKEN MEAT AND ANTIOXIDANT ACTIVITY OF THEIR ISOLATES - Okarini, I. A; Purnomo, Heri; -, Aulanni'am; Eka Radiati, Liliek; Lindawati, S. A; Miwada, I N.S (Jurnal Peternakan Tropika, 2020)
The lactic acid bacteria (LAB) of bebontot or buntilan (Balinese traditional meat fermented product) of chicken breast meat of spent laying hen had been identified and these LAB were distributed as 58.33%  Pediococcus acidilactici strain LMG 17680 and 41.67%  Pediococcus acidilactici strain O-mls-1 at 0 day of the batters. The result observed at the end of fermentation (5 days) dried under the sun were isolate consist of 56.25% Pediococcus pentosaceus strain Ni 1386; 20.83% Lactobaccillus plantarum strain PA21 and 8.33% Lactobacillus plantarum strain Ni 1002. The average inhibition concentration (IC)  of  radical scavenging  activity (RSA) of 1.1-diphenyl-2-picrylhydrazyl, DPPH after innoculation (0 day) was 66.83±3.55% and after 5days of fermentation was  83.37±4.06%. It is interesting to note that LAB isolates of bebontot   spent-hen chicken breast meat of properness (nor isolated from human or infant feces) and could be benefit for antioxidant activity to process functional meat products for human consumption. Keywords: Identification, antioxidant activity, LAB isolates, bebontot